RUMAH EDUKASI KELOLA SAMPAH DAN SADAR IKLIM (RESIK) SEBAGAI UPAYA MEWUJUDKAN DESA KETAHANAN BENCANA DI DESA BOJONG KULUR, PROVINSI JAWA BARAT - Dyah Kristyowati; Resty Widya Kurniasari; Jordy Satria Widodo; Puji Rahayu; Alo Karyati; Qotrunnadya Khusnul Wardati; Rachel Amtul Noor (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This article discusses the establishment of a waste management and climate awareness program ("RESIK") as an effort to create a disaster-resilient village in Bojong Kulur. The program addresses issues such as recurring floods, low public awareness of waste management, and the impending closure of the Bantargebang landfill. The objective of this service is to increase public awareness of climate issues, improve waste management capabilities, create environmentally friendly settlements, and establish a circular management system. The method used is mentoring and technology implementation for Youth Groups, PKK, Women Farmers Groups, and Waste Bank Managers. The results achieved were the implementation of interventions in the form of a digital waste bank, an IoT-based dropbox, and a plastic shredding machine. This program highlights the importance of community involvement and pentahelix collaboration to achieve sustainable economic benefits through waste processing.